Electrochemical Reduction Behaviour of Zileuton at a Dropping Mercury Electrode by Polarography - N. Y. Sreedhar; M. Sankara Nayak; K. Srinivasa Prasad; P. R. Prasad; C. Nageswar Reddy (E-Journal of Chemistry)
Electrochemical behaviour of anticancer drug zileuton was investigated by direct current polarography (DCP) and differential pulse polarography using a dropping mercury electrode (DME) as working electrode and Ag/AgCl reference electrode in universal buffer of pH range from 2.0 to 12.0. The drug was extracted from the dosage forms in dimethyl formamide (DMF). Kinetic parameters such as diffusion co-efficient (D) and heterogeneous forward rate constants (k0f,h) are evaluated and reported. The differential pulse polarographic method has been developed for the determination of this drug in pharmaceutical formulations.